Graphic Narratives of Women in War: Identity Construction in the Works of Zeina Abirached, Miriam Katin, and Marjane Satrapi - Szép, Eszter (International Studies. Interdisciplinary Political and Cultural Journal, 2014)
By applying terminology from trauma theory and a methodological approach from comics scholarship, this essay discusses three graphic autobiographies of women. These are A Game for Swallows by Zeina Abirached (trans. Edward Gauvin, 2012), We are on our Own by Miriam Katin (2006), and Persepolis by Marjane Satrapi (trans. Anjali Singh, 2004). Two issues are at the centre of the investigation: the strategies by which these works engage in the much-debated issues of representing gendered violence, and the representation of the ways traumatized daughters and their mothers deal with the identity crises caused by war.